Kombinasi Sistem Solar Tracker Dua Sumbu dan Automatic Transfer Switch (ATS) untuk Menstabilkan Tegangan Keluaran Pembangkit Photovoltaic (PV) Menggunakan Sensor Photodioda dan Arduino Nano - Agung Hadi Tamari; Amirullah Amirullah (Rekayasa, 2022)
The performance of a photovoltaic (PV) generator is strongly influenced by the intensity of sunlight hitting the solar module. Thus it takes the position of the solar module which is always perpendicular to the direction of the sun's rays. To overcome this, it is necessary to design and implement a two-axis solar tracker system using a servo motor that is able to dynamically drive a PV generator following the direction of movement of sunlight supplied by an AC power source (PLN). The problem is that if the AC source is disturbed, the motor drive stops working so that the absorption of sunlight is not optimal. The research proposes the design and implementation of a two-axis solar tracker system based on Arduino Nano using a photodiode sensor and automatic transfer switch (ATS). ATS functions if there is a disturbance in the AC source, the system automatically transfers the load power supply to a DC source in the form of a battery or vice versa, so that the tool is still able to work. The photodiode sensor in the Arduino Nano circuit is used because it has better sensitivity to sunlight than the light-dependent resistor (LDR) sensor. The PV generator in this study uses the PV1 and PV2 modules. The results shows that the PV module using a two-axis tracker system with dynamic movement following the movement of the sun's position is able to produce a more significant and more stable average output voltage-than the system without using a tracker both on the static PV module position facing east and west respectively by 12.34% and 10.94%. The sensitivity of the photodiode sensor to sunlight also helps improve the performance of the proposed system so that the PV output voltage in the 09.00-15.00 WIB period, becomes larger and more stable than the system without a solar tracker.